Pre-Announcement Price Dynamics in Nordic Follow-on Equity Offerings : Evidence of Directed Share Issues and Accelerated Bookbuildings - Hirvonen, Lassi (My University, 2025)
This thesis investigates whether Nordic follow-on equity offerings executed through accelerated bookbuildings and directed share issues exhibit systematic short-horizon pricing dynamics prior to public disclosure. The inquiry is motivated by the conceptual tension within the literature on issuance timing: information-asymmetry models, behavioural pricing mechanisms, market-efficiency arguments and rational real-options frameworks generate diverging expectations for pre-announcement return behaviour, and none yields a definitive prediction in the Nordic institutional setting. The Nordic markets combine high transparency, dense institutional monitoring and rapid execution mechanisms, implying that any informational or behavioural frictions capable of generating short-term valuation deviations are confined to a narrowly bounded preannouncement window. Methodologically, the study applies a short-horizon event-study design that estimates market-model abnormal returns over a pre-announcement period ending immediately before disclosure. Using a hand-collected sample of 40 offerings issued between 2007 and 2025, the analysis integrates both time-series evidence on cumulative return patterns and cross-sectional diagnostics based on firm-level idiosyncratic volatility. This framework enables the identification of valuation drift, the assessment of its heterogeneity across informational environments and the evaluation of how efficiently the market incorporates issuance information once it becomes public. The results indicate that short-lived pricing deviations arise exclusively within the pre-announcement window. A smooth and temporally distributed upward drift appears before disclosure, while announcement-day and post-announcement abnormal returns remain statistically indistinguishable from zero. This asymmetric pattern suggests that investors form expectations under partial or unevenly processed information prior to the event, but that any interpretive ambiguity is eliminated once definitive issuance information is released. Crosssectional evidence provides modest support for the view that informational frictions condition the magnitude of pre-announcement effects, although these frictions do not persist beyond disclosure. Taken together, the findings refine theoretical understanding of issuance timing in the Nordic context by demonstrating that temporary valuation effects originate within and are confined to the informational ambiguity preceding public announcement. The study thereby clarifies the empirical preconditions under which timing incentives may become relevant and provides a framework for interpreting short-horizon pricing behaviour in markets characterised by both high transparency and rapid execution.

Tutkielma tarkastelee, esiintyykö Pohjoismaissa toteutetuissa listayhtiöiden myöhemmissä osakeanneissa systemaattisia lyhyen aikavälin tuottopoikkeamia ennen annin julkista ilmoittamista. Tutkimus kohdistuu erityisesti nopeutettua tarjousmenettelyä ja suunnattuja osakeanteja hyödyntäviin järjestelyihin, joissa annin toteutus tapahtuu nopeasti rajatulle sijoittajaryhmälle. Tutkimusaihe pohjautuu liikkeeseenlaskun ajoitusta käsittelevän kirjallisuuden sisäiseen teoreettiseen jännitteeseen: informaation epäsymmetriaan perustuvat mallit, käyttäytymispohjaiset hinnoittelumekanismit, markkinatehokkuutta korostavat näkökulmat sekä rationaalisiin reaalivaihtoehtoihin nojaavat viitekehykset tuottavat keskenään ristiriitaisia odotuksia ilmoitusta edeltävästä tuottokäyttäytymisestä. Yksikään näistä viitekehyksistä ei kuitenkaan anna yksiselitteistä ennustetta Pohjoismaiden institutionaalisessa ympäristössä, jota luonnehtivat korkea läpinäkyvyys, tiivis institutionaalinen seuranta ja poikkeuksellisen nopeat toteutusmekanismit. Näin ollen mahdollisten informaatio- tai käyttäytymisperäisten ilmiöiden on synnyttävä ja purkauduttava hyvin rajatussa ikkunassa, jotta ne voisivat ilmetä havaittavina lyhytaikaisina arvostuspoikkeamina. Menetelmällisesti tutkielma hyödyntää lyhyen aikavälin tapahtumatutkimus -asetelmaa, jossa markkinamalliin perustuvat epänormaalit tuotot estimoidaan ilmoitusta edeltävältä ajanjaksolta. Aineisto koostuu käsin kootusta 40 osakeannin otoksesta vuosilta 2007–2025. Asetelma yhdistää kumulatiivisten tuottokehitysten aikasarja-analyysin ja poikkileikkaustarkastelun, jossa yrityskohtaisia idiosynkraattisen volatiliteetin mittareita hyödynnetään informaatioympäristöjen erojen tunnistamisessa. Empiiriset tulokset osoittavat, että lyhytaikaiset hinnoitteluvaikutukset rajoittuvat yksinomaan ilmoitusta edeltävään ajanjaksoon. Ennen julkistusta havaitaan tasainen positiivinen tuottokehitys, kun taas ilmoituspäivän ja sitä seuraavien päivien epänormaalit tuotot eivät ole tilastollisesti merkitseviä. Tämä viittaa siihen, että sijoittajien odotukset muotoutuvat ennen tapahtumaa epäselvän tai osittaisen informaation varassa, mutta purkautuvat välittömästi annin julkistamisen myötä. Kokonaisuutena tulokset täsmentävät liikkeeseenlaskun ajoitusta koskevaa teoreettista ymmärrystä Pohjoismaiden kontekstissa osoittamalla, että lyhytikäiset arvostusvaikutukset syntyvät vain ennen julkista ilmoitusta vallitsevan informaatioepäselvyyden aikana ja rajoittuvat siihen.
Keywords: Follow-on Public Offering (FPO), Directed Share Issue, Accelerated Bookbuilding (ABB), Market Timing, Mispricing, Information Asymmetry, Behavioural Finance, Cumulative Abnormal Return (CAR), Listayhtöiden myöhemmät osakeannit, Suunnattu osakeanti, Kiihdytetty tarjousmenettyely, Markkina-ajoitus, Virhehinnoittelu, Informaation epäsymmetria, Käyttäytymisrahoitus, Kumulatiivinen epänormaali tuotto